Bundle Payment, Health Care Utilization, and Outcomes Following Surgery for Anterior, Middle, and Posterior Cranial Fossa Skull Base Meningioma: A Market Scan Analysis. (1st September 2019) - Sharma, Mayur; Ugiliweneza, Beatrice; Boakye, Maxwell; Andaluz, Norberto O; Williams, Brian J
Abstract: INTRODUCTION: Meningioma is the most common benign intracranial brain tumor accounting for approximately one-third of all primary brain tumors. The aim of our study was to compare the bundle payment, health care utilization, and outcomes following surgery for anterior (AFM), middle (MFM), and posterior cranial fossa meningioma (PFM) across the United States. METHODS: We queried the Market Scan database using ICD-9 and CPT-4, from 2000 to 2016. We included adult patients who had at least 24 mo of enrollment following the surgical procedure. The outcome of interest was length of hospital stay, disposition, complications, and reoperation following the procedure. RESULTS: A cohort of 1, 188 patients was identified from the database. In all 43.86% of tumors were AFM, 32.32% were MFM, and only 23.8% were PFM. Patients who underwent surgery for PFM had significant longer hospital stay ( P  = .0013), higher complication rate ( P  = .0009), and less likely to be discharged home ( P  = .0013) during index hospitalization. Patients with MFM and PFM incurred higher outpatient services with no differences in corresponding payments compared to those with AFM at 12 mo ( P  < .0001) and 24 mo follow-up ( P  < .0001). There were no differences in overall payments at 12 mo (AFM: $19, 702; MFM: $20, 671; PFM: $20, 922) and 24 mos (AFM: $37, 142; MFM: $44, 133; PFM: $36, 601) among the cohorts. There was no significant difference in 90-d median bundle payments among the groups, $66, 173 (AFM) vs $65, 602 (MFM), and $71, 837 (PFM), P  = .1955. CONCLUSION: Ninety-day bundle payment and overall payments (at 12 mo and 24 mo) were not significantly different among the cohorts. Patients with PFM had longer hospital stay, higher complication rate, and less likely to be discharged home with higher utilization of outpatient services at 12 mo and 24 mo.